Effect of mHealth on modifying behavioural risk-factors of non-communicable diseases in an adult, rural population in Delhi, India - Sharma, Malvika; Banerjee, Bratati; Ingle, G.K.; Garg, Suneela (mHealth, 2017)
Background: The rising trend of non-communicable diseases (NCDs) has led to a “dual burden” in low and middle-income (LAMI) countries like India which are still battling with high prevalence of communicable diseases. The incorporation of a target specially dedicated to NCDs within the goal 3 of the newly adopted Sustainable Development Goals indicates the importance the world now accords to prevention and control of these diseases. Mobile phone technology is increasingly viewed as a promising communication channel that can be utilized for primary prevention of NCDs by promoting behaviour change and risk factor modification. Methods: A “Before and After” Intervention study was conducted on 400 subjects, over a period of one year, in Barwala village, Delhi, India. An mHealth intervention package consisting of weekly text messages and monthly telephone calls addressing lifestyle modification for risk factors of NCDs was given to the intervention group, compared to no intervention package in control group. Results: After Intervention Phase, significant reduction was seen in behavioural risk factors (unhealthy diet and insufficient physical activity) in the intervention group compared to control group. Body mass index (BMI), systolic blood pressure and fasting blood sugar level also showed significant difference in the intervention group as compared to controls. Conclusions: Our study has demonstrated the usefulness of mHealth for health promotion and lifestyle modification at community level in a LAMI country. With the growing burden of NCDs in the community, such cost effective and innovative measures will be needed that can easily reach the masses.